Competition Issues in Restructuring Ports and Railways, Including Brief Consideration of these Sectors in India - Russell Pittman (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2009)
One important issue facing reformers considering the restructuring of the seaports and freight railways sectors of a developing country is the creation of competition or, alternatively, avoiding the creation or preservation of monopoly power. In seaports a crucial distinction is often that between intraport and interport competition; in freight railways, between competition among train operating companies over a monopoly track and competition among vertically integrated railways. In both cases it is useful to frame the issue as one of competition at the component level within an open system versus competition between closed systems. In both cases as well, the market definition paradigm suggested by the Horizontal Merger Guidelines of the U.S. competition agencies provides a useful framework for analysis.
Keywords: L14; L23; L33; L91; L92; O14; O22; R48; 330; competition; ports; railways; market definition; India